Effects of informal communication on happiness at the workplace and job performance of employees - Chunin, Manop (Kasetsart Journal of Social Sciences, 2018)
The first phase of the investigation involved documentary research to study the roles of informal communication. The research results revealed 11 roles of informal communication. The second phase of the research was experimental research using a pretest-posttest control design. The objective of this phase was to compare happiness in the workplace and the job performance of employees between the experimental group and the control group both before and after the experiment. Treatment of this experiment was through informal communication involving permission to have general conversations and questions and answers. The experimental results showed that the experimental and control groups had different levels of happiness in the workplace with a statistical significance of .01. The employees in the experimental group were happier than the employees in the control group. However, there was no difference in the levels of job performance between the employees in the two groups. The third phase of the investigation was qualitative research using focus group discussion and interview methods. The objective of this phase was to explore informal communication by considering the senders, message, channel, receivers, and feedback and how these affected happiness in the workplace and the job performance of employees. The key informants were 12 employees in the experimental group from the second phase. The research results revealed senders, message, channel, receivers, and feedback on informal communication affected happiness in the workplace and the job performance of employees.